2016
DOI: 10.3390/biomedicines4030022
|View full text |Cite
|
Sign up to set email alerts
|

An Abraded Surface of Doxorubicin-Loaded Surfactant-Containing Drug Delivery Systems Effectively Reduces the Survival of Carcinoma Cells

Abstract: An effective antitumor remedy is yet to be developed. All previous approaches for a targeted delivery of anticancer medicine have relied on trial and error. The goal of this study was to use structural insights gained from the study of delivery systems and malignant cells to provide for a systematic approach to the development of next-generation drugs. We used doxorubicin (Dox) liposomal formulations. We assayed for cytotoxicity via the electrical current exclusion method. Dialysis of the samples yielded infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, the Guinier–Porod exponent, providing information on the nanoparticle surface, remained the same: −4.0 (NLC) and −4.2 (NLC BZC ) at 25, 37, and 40 °C. According to it, both NLC and NLC BZC exhibited smooth surfaces, which can indicate drug dispersion into the lipid matrix, without the adsorption of unencapsulated molecules in the nanocarrier surface . BZC did not change the radius of gyration nor change the surface of the nanoparticle, as observed in other NLC systems, confirming the dispersion of the anesthetic inside the nanoparticles.…”
Section: Resultsmentioning
confidence: 59%
“…Interestingly, the Guinier–Porod exponent, providing information on the nanoparticle surface, remained the same: −4.0 (NLC) and −4.2 (NLC BZC ) at 25, 37, and 40 °C. According to it, both NLC and NLC BZC exhibited smooth surfaces, which can indicate drug dispersion into the lipid matrix, without the adsorption of unencapsulated molecules in the nanocarrier surface . BZC did not change the radius of gyration nor change the surface of the nanoparticle, as observed in other NLC systems, confirming the dispersion of the anesthetic inside the nanoparticles.…”
Section: Resultsmentioning
confidence: 59%
“…To illustrate the point from another perspective, material sciences, in this case developing formulations for anti-cancer-medication, relies upon the principle of trial and error. However, one publication suggests an alternative path [17]. The authors are not going so far as to suggest they found the holy grail, but getting a sense of how to streamline the pipeline would probably be seen as advantageous by many.…”
Section: Discussionmentioning
confidence: 99%